A comprehensive optimization framework for the design of high-performance building systems. (15th April 2023) - Zeng, Zhaoyun; Lu, Di; Hu, Yuqing; Augenbroe, Godfried; Chen, Jianli
Abstract: Improving the performance of buildings is crucial to achieving the Paris Agreement's goal of limiting global warming to 1.5 °C. Optimization is critical to ensuring that buildings achieve the desired performance. In the literature, a systematic discussion on the interdependences between the objective functions, constraints, and design variables is missing. In this work, we try to fill this research gap by presenting a comprehensive optimization framework for the design of high-performance building systems. This framework provides a systematic and detailed introduction to each step of formulating and solving optimization problems. Two application studies are also presented to demonstrate how this optimization framework can be used in practical applications. The first study demonstrates how to construct cost models and handle optimization problems with economy objective functions, and the second study demonstrates how to solve multi-objective optimization problems with a-posteriori-articulation methods to generate the Pareto optimal set. This paper can serve as a guide for future researchers and designers by providing them with a basic problem-solving procedure and helping them avoid common mistakes. Highlights: An optimization framework is proposed for high-performance building systems. The interdependences between different elements of formulation are discussed. Two application studies are presented to demonstrate the optimization framework. This framework can serve as a guide for readers to help them avoid common mistakes.